Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

A visual analysis of gender bias in contemporary anatomy textbooks - Parker, Rhiannon; Larkin, Theresa; Cockburn, Jon (Social Science & Medicine, 2017)
Les recherches empiriques ont établi un lien entre les préjugés sexistes dans l’enseignement médical et les attitudes et comportements négatifs des prestataires de soins de santé. Pourtant, cela fait plus de 20 ans que les recherches n’ont pas examiné dans quelle mesure les femmes et les hommes sont représentés de manière égale dans les manuels d’anatomie . En outre, les recherches antérieures n’ont pas exploré au-delà de la quantité de représentation pour examiner également les stéréotypes visuels de genre et, à la lumière des avancées théoriques dans le domaine de la recherche intersectionnelle, la relation entre les représentations du genre et les représentations de l’ethnicité, du type de corps, de la santé et de l’âge. Cette étude visait à déterminer l’existence et la représentation des préjugés sexistes dans les principaux manuels d’anatomie utilisés dans les écoles de médecine australiennes. Une analyse systématique du contenu visuel a été menée sur 6044 images dans lesquelles le sexe/genre pouvait être identifié, provenant de 17 principaux manuels d’anatomie publiés entre 2008 et 2013. Une analyse de contenu plus approfondie a été réalisée sur les 521 images narratives, qui représentent une histoire en cours, trouvées dans les mêmes manuels. Les résultats indiquent que la représentation du genre dans les images des manuels d’anatomie reste majoritairement masculine, sauf dans les sections spécifiques au sexe. En outre, d’autres formes de biais ont été constatées dans : la visualisation d’émotions, de rôles et de contextes stéréotypés en fonction du sexe ; le manque de diversité ethnique, d’âge et de type corporel ; et dans l’adhésion presque totale à une conception binaire sexe/genre. Malgré une attention accrue portée aux questions de genre en médecine, la représentation visuelle du genre dans les programmes médicaux continue d’être biaisée. La construction biaisée du genre dans les manuels d’anatomie conçus pour l’enseignement médical fournit aux futurs prestataires de soins de santé des informations inadéquates et irréalistes sur les patients.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; australie; corps; discous dominant; intersectionnalité; livres d'anatomie; océanie; projet charge mentale; périodes historiques; racisme; représentation des corps; régions géographiques; santé; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques

Transcultural bodies: female genital cutting in global context - Hernlund, Ylva; Shell-Duncan, Bettina (Rutgers University Press, 2007)
Female "circumcision" or, more precisely, female genital cutting (FGC), remains an important cultural practice in many African countries, often serving as a coming-of-age ritual. It is also a practice that has generated international dispute and continues to be at the center of debates over women's rights, the limits of cultural pluralism, the balance of power between local cultures, international human rights, and feminist activism. In our increasingly globalized world, these practices have also begun immigrating to other nations, where transnational complexities vex debates about how to resolve the issue. Bringing together thirteen essays,Transcultural Bodiesprovides an ethnographically rich exploration of FGC among African diasporas in the United Kingdom, Europe, and Australia. Contributors analyze changes in ideologies of gender and sexuality in immigrant communities, the frequent marginalization of African women's voices in debates over FGC, and controversies over legislation restricting the practice in immigrant populations.
Keywords: afrique; anthropologie; approches et analyses; australie; corps; cours; discipline; europe; histoire et politique; océanie; premier cycle; racisme; ressource en ligne; royaume-uni; régions géographiques; santé; sciences humaines; sex2283; sexisme; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; transculturalisme; violences

The Quest for Modern Manhood: Masculine Stereotypes, Peer Culture and the Social Significance of Homophobia - Plummer, David C. (Journal of Adolescence, 2001)
This paper explores the use of homophobic terms by boys and young men and the meanings they invoke when using them. Highly detailed interviews were conducted with young men from diverse backgrounds about their own experiences while growing up and their observations of schools, teachers, family and peers. Homophobia was found to be more than a simple prejudice against homosexuals. Homophobic terms like “poofter” and “faggot” have a rich developmental history and play a central role in adolescent male peer-group dynamics. Homophobic terms come into currency in primary school. When this happens, words like poofter and faggot rarely have sexual connotations. Nevertheless, far from being indiscriminate terms of abuse, these terms tap a complex array of meanings that are precisely mapped in peer cultures, and boys quickly learn to avoid homophobia and to use it decisively and with great impact against others. Significantly, this early, very powerful use of homophobic terms occurs prior to puberty, prior to adult sexual identity and prior to knowing much, if anything, about homosexuality. An effect of this sequence is that early homophobic experiences may well provide a key reference point for comprehending forthcoming adult sexual identity formation (gay or not) because powerful homophobic codes are learned first.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; australie; cours; discipline; homophobie; hétérosexisme; masculinité; nouvelle-zélande; océanie; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences